PENGELOLAAN BANK SAMPAH DALAM MENUMBUHKAN PELUANG USAHA NASABAH BANK SAMPAH - Suciati Muanifah; Yenni Cahyani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This research focus on how the management of waste banks in growing business opportunities for waste bank customers. The objectives of this research are: (1) to explain the waste bank management (2) to explain the business opportunities of Asri Berseri Pamulang waste bank customers (3) to explain the community's skills with the Asri Berseri Pamulang waste bank. This research is a descriptive qualitative research with data collection methods in the form of in-depth interviews, observation and documentation. The data processing and analysis starts from transcribing, labeling, grouping, comparing, and contrasting and interpreting. The results of this study indicate that the management of the Asri Berseri waste bank can actually foster business opportunities and skills for waste bank customers and the public. Since the existence of the Asri Berseri waste bank, the waste produced by the community is better managed, namely by sorting waste, so that the community gets benefits from the waste generated, including: (1) business opportunities from waste products (2) skills to recycle waste into handicraft items